2014
DOI: 10.5826/dpc.0403a02
|View full text |Cite
|
Sign up to set email alerts
|

The dermatoscopic universe of basal cell carcinoma

Abstract: Following the first descriptions of the dermatoscopic pattern of basal cell carcinoma (BCC) that go back to the very early years of dermatoscopy, the list of dermatoscopic criteria associated with BCC has been several times updated and renewed. Up to date, dermatoscopy has been shown to enhance BCC detection, by facilitating its discrimination from other skin tumors and inflammatory skin diseases. Furthermore, upcoming evidence suggests that the method is also useful for the management of the tumor, since it p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
159
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(179 citation statements)
references
References 68 publications
11
159
0
9
Order By: Relevance
“…Interestingly, only a minority of BCCs were clinically pigmented in our study sample, which is in accordance with previous reports showing that pigmented BCCs are mostly located on the trunk [11]. Furthermore, even though dermoscopy is known to increase the number of pigmented BCCs by detecting clinically undetectable pigmented criteria, only few of our lesions displayed those criteria, which were mostly classified as melanoma-looking lesions [17,18]. Results of multivariate analysis showed that the following dermoscopic criteria were independently associated with malignant-looking BCCs: erosions/ulceration and vessels.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, only a minority of BCCs were clinically pigmented in our study sample, which is in accordance with previous reports showing that pigmented BCCs are mostly located on the trunk [11]. Furthermore, even though dermoscopy is known to increase the number of pigmented BCCs by detecting clinically undetectable pigmented criteria, only few of our lesions displayed those criteria, which were mostly classified as melanoma-looking lesions [17,18]. Results of multivariate analysis showed that the following dermoscopic criteria were independently associated with malignant-looking BCCs: erosions/ulceration and vessels.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies suggest that dermoscopy significantly facilitates the accurate management of this tumour [21]. In detail, the dermoscopic criteria associated with non-pigmented BCC include fine telangiectasias with few ramifications and/or multiple small erosions for the superficial subtype, and classical arborizing vessels and large ulceration/s for the nodular subtype (Fig.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…Pigmented BCC is dermoscopically typified by brown-coloured structures, including leaf-like areas, spoke wheel areas, or concentric structures, predictive of pigmented superficial BCC, and large blue-grey ovoid nests predictive of a non-superficial (i.e., invasive, nodular) subtype [22]. BCC with an infiltrative component often exhibits fine scattered telangiectasias and white/red structureless areas, whereas morphoeic (sclerodermiform) BCC frequently displays a whitish background, corresponding histologically to the underlying dermal fibrosis [21,23]. …”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…These are known features of basal cell carcinoma. 6 However dermoscopy of basal cell carcinoma in radiation-exposed areas was not described previously. With the new and recent knowledge about dosage and appropriate radiotherapy management, fewer adverse effects would be expected, so that its benefits increasingly outweigh its risks.…”
Section: Discussionmentioning
confidence: 98%